Faktor-Faktor Yang Berhubungan Dengan Pemberian Asi Bersamaan Makanan Tambahan Pada Bayi 0-6 Bulan Di Wilayah Kerja Puskesmas Kota Manna Bengkulu Selatan - Nuril Absari; Mika Oktarina; Choralina Eliagita; Nenda Puryanti; Devi Hartanti (Jurnal Kesehatan Medika Udayana, 2022)
Background : The benefits of breast milk will increase if the baby is only given breast milk for the first six months of life. Purpose : This study aims to study the factors associated with breastfeeding along with supplementary feeding in infants 0-6 months in the Work Area of ??Manna City Health Center in South Bengkulu. This research approach uses descriptive with cross sectional design. Methods :The population in this study were all mothers who had infants aged> 6-12 months in the work area of ??Manna City Health Center as many as 112 people, obtained 50 samples using Accidental Sampling. The data used are primary virgin and secondary data. Data were analyzed using univariate and bivariate analysis with Chi-Square test (?2) and Contingency Coefficient Test (C). Results : The results of the study were obtained from 50 people, there were 33 people (66.0%) giving ASI together with additional meals, 22 people (44.0%) having secondary education, 22 people (44.0%) having less knowledge, 27 people (54.0 %) health workers support, Conclusion : there is a significant relationship between education and concurrent breastfeeding supplementary food in infants 0-6 months with a weak relationship category, there is a significant relationship between knowledge with concurrent breastfeeding supplementary food in infants 0-6 months with moderate relationship categories, there is a significant relationship between the support of health workers with breastfeeding together with additional food for infants 0-6 months with a weak relationship category. It is expected that health workers can increase counseling to increase the knowledge of pregnant and lactating mothers about the right time to provide additional food and the importance of conducting regular Classroom and Posyandu visits.